MYCOREMEDIATION OF BISMARCK BROWN Y BY INDIGENOUS FUNGAL ISOLATE ALTERNARIA BRASSICAE TSF – 07 AND OPTIMIZATION OF CULTURAL CONDITIONS TO ENHANCE ITS DECOLOURIZATION - KANYAKUMARI P. SHINDE,; P. R. THORAT, (International Journal of Pharma and Bio Sciences, 2013)
Bismarck Brown Y was selected as model textile dye. The fungal strain Alternaria brassicae TSF – 07 isolated from textile wastewater sludge was screened for decolourization of Bismarck Brown Y. Optimization was carried out with respect to carbon source, nitrogen source, pH, inoculums size, incubation period and temperature. It was found that the optimum inoculum size, pH and temperature were 2.5%, 5.0 and 350C respectively. Fructose at 1.0 % and yeast extract at the concentration of 0.1 % was found to give maximum decolourization. Further, it was found that the culture has brought about almost 96.03% decolourization of a recalcitrant dye, Bismarck Brown Y (100 mgL-1) at shaking condition within 3 days. This isolate also showed the degradation as evidenced from the reduction in the term of COD mg/L to the extent of 68.09 % within three days. The biodegradation was monitored by UV–Vis and FTIR spectroscopy.This study revealed the enormous biodegradation abilities of indigenous microbial flora.